2017
DOI: 10.1109/tuffc.2017.2709623
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of a 20-MHz Microlinear Phased-Array Transducer for Intervention Guidance

Abstract: This paper describes the design and fabrication of a miniature ultrasonic phased array transducer used for intervention guidance. Currently ultrasound probes are often placed at the body surface of the patients, leading to several drawbacks including the limitation of penetration and image quality. In order to improve the reliability of the guiding process, we propose a miniature phased array transducer that can be placed adjacent to the intervention device during the interventional procedure. In this paper, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Both liver and hepatic stimulation experiments were performed with portions of the stimulation ultrasound beam extending slightly beyond the target organ (approximately, 2 mm beyond the organ for splenic stimulation and <0.5 mm for hepatic stimulation). Application of new ultrasound transducer technology may be utilized in future experiments to increase the level of stimulus precision 48 50 . Still, the data herein represents the first report in which a targeted ultrasound tool enabled stimulation of multiple points within a single organ (i.e., stimulation of the porta hepatis region versus right or left lobe, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Both liver and hepatic stimulation experiments were performed with portions of the stimulation ultrasound beam extending slightly beyond the target organ (approximately, 2 mm beyond the organ for splenic stimulation and <0.5 mm for hepatic stimulation). Application of new ultrasound transducer technology may be utilized in future experiments to increase the level of stimulus precision 48 50 . Still, the data herein represents the first report in which a targeted ultrasound tool enabled stimulation of multiple points within a single organ (i.e., stimulation of the porta hepatis region versus right or left lobe, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was reported by Ritter et al [27] of an effective element width 16% larger than the actual element width for a 30-MHz linear array with maximum crosstalk < −30-dB and −6-dB directivity of ±20°. Similarly, Chiu et al [28] reported a −6-dB directivity of approximately ±20°for a 20-MHz phased array with maximum crosstalk < −28 dB.…”
Section: Single-element Azimuthal Directivity Responsementioning
confidence: 78%
“…where is the center frequency, VT and VR are the transmitting and receiving amplitudes, and is the distance between the target and transducer. The IL value of the phased array elements was measured to be −19.7 dB, which is superior to those of PMN-PT single crystal-and PZT-5H-based high frequency (≥20 MHz) phased arrays [18,19,20]. This phenomenon is probably related to the high Curie Temperature of PIN-PMN-PT single crystal.…”
Section: Characterization and Discussionmentioning
confidence: 86%
“…Currently, to the best of our knowledge, single element transducers and linear arrays are widely used [14,15,16,17]. Only a few studies have been carried on the high-frequency ultrasound phased array [18,19,20,21], though it is very useful in biomedical imaging by providing electronic-beam-focusing and steering capabilities. Furthermore, there are even fewer researches on composite-material-based high-frequency ultrasound phased arrays, despite the numerous benefits of composite piezoelectric materials (lower acoustic impedance, higher electromechanical coefficient, broader bandwidth, etc.).…”
Section: Introductionmentioning
confidence: 99%